Crianças, jovens e literatura: produto de pesquisa patrocinada pelo INEP-INL/FNLIJ - Pires, Nise (1976)
There is a general impression that reading habits have been disappearing. However, McLuhan, himself states that the values associated to the written and printed word should be permanent element of the human heritage. More important than to discuss the book disappearance or its transformations it is to investigate what is occurring with the new generations, in this changing society, regarding reading in general, and reading literature specifically. The research problem was formulated as follows: What are the tipical reading behaviors of students enrolled in fundamental education of schools located in the city of Rio de Janeiro, regarding literature? To answer the question, students were described as readers; home and school were described according to their level of reading stimulation; and libraries and bookstores were characterized as to their book access facilities. The methodology herein adopted was especially designed for the study and therefore is tentative. The results indicated that the students read an insufficient number of literary books and that comics evidenced the highest level of consumption among the students. In addition, the students appeared to be reading at levels inferior to their levels of cognitive development. It was assumed that they were highly influenced by the mass media. In general, home and school did not appear to be offering conditions to stimulate the students reading habits. The number of libraries was insufficient to attended the real and potential readers. Bookstores did not seem to be concerned with helping their clientele of children and youngsters. A positive relationship was found between reading habits/reading interest and (a) home and school characteristics and, (b) access facilities to books. A situation was configurated in which to a degradation of the written literature corresponded an increasing domination of mass media. Such a fact was taken as representing a universal trend, derived from the current stage of mankind. Suggestions were offered, followed by an operationalization of activities, and may represent means to attenuate the identified deficiencies and offer aids to book policies that aim at developing an integrated program to stimulate the books levels of consumption, production and dissemination.